Implementasi Pembelajaran Bahasa Arab Berbasis Pendekatan Kontekstual dan Buku Teks Kontekstual Perguruan Tinggi - Guettaoui Bedra, Kddour; Febriani, Suci Ramadhanti (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2022)
Arabic language learning program are implemented for all students under the auspices of the Language Development Center in UIN Imam Bonjol Padang. This program aims to increase foreign language skills; listening, speaking, reading and writing skills. So, the output of this program is expected that students can dig up information to support global communication. This study aims to describe Arabic language learning based on contextual approach and contextual textbook as well as factors that influence the success of the Arabic learning process at the UIN Imam Bonjol Padang. This research used a qualitative approach with case study method through data collection including observation, interview and documentation. The results showed that Arabic language learning based on contextual learning is suitable for universities, supported by using of interactive teaching materials equipped with exercises, as well as an intense duration of time so that it is very effective to improve the skills of student’s UIN Imam Bonjol Padang. This research strengthens the importance of using daily contextual conditions in Arabic language learning so that students can practice their daily language skills with the surrounding environment.